A Corporate Purpose as an Antecedent to Employee Motivation and Work Engagement - van Tuin, Lars; Schaufeli, Wilmar B.; Van den Broeck, Anja; van Rhenen, Willem (Frontiers in Psychology, 2020)
It is generally assumed that a corporate purpose aiming to benefit all stakeholders has a positive effect on employee motivation and engagement, but no empirical studies into these specific effects were found. To examine this assumption, a corporate mission and vision matching the definition of a higher purpose were tested in two subsequent studies. The first study (N = 270) was a cross-sectional self-report study. The second study included a longitudinal design (N = 56) modeling purpose, motivation, and engagement in a cross-lagged panel design over three time-points. The results associated purpose with motivation and engagement. The subsequent longitudinal analysis confirmed the presumed directionality from purpose to engagement, but not to motivation. Hence, while a corporate purpose can be added to the list of antecedents to work engagement, the relationship with motivation, despite the significant association with purpose in the cross-sectional study, remains more complicated. The present study adds to the knowledge of the beneficial effects of a broader purpose and responds to the current surge of interest in purpose as an instrument for sustainable business.